IDENTIFYING EFFECTIVE FACTORS IN THE IMPLEMENTATION OF E-COACHING IN SMALL AND MEDIUM ORGANIZATIONS IN THE FOOD INDUSTRY - Mahan Hassani; Dr. Alireza Motameni (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2022)
One of the most important and effective factors in organizations is the amount of knowledge, experience, and professionalism, leading to comparative advantage and business success. Business owners and young executives are constantly facing micro-problems. These micro-problems are, in fact, themselves the result of fundamental challenges. Instead of professionally identifying and overcoming root barriers, they often try to resolve the effects of these root deficiencies. As technology grows, the competition in the industry increases, and the market becomes more specialized. At the same time, entering a competitive market is more difficult than ever. One of the problems for start-ups to enter the market is management problems and consequently human resources problems. These challenges can be minimized by using cyber-space and online coaches. This paper aims to identify the factors affecting the implementation of e-coaching in small and medium organizations in the food industry. This research is considered as development-based and applied research in terms of purpose. The research method is a combination of survey methods and descriptive-analytical methods. The tools used in the research are questionnaires and interviews. The questionnaire used in this study is a fuzzy Delphi questionnaire for pairwise comparisons and ranking of factors. After studying the libraries-based resources and interviewing the experts, we identified 25 factors and provided them in 37 questions. Finally, after performing the fuzzy Delphi method, 16 effective factors were identified for the final ranking. After ranking 16 effective indicators, suggestions were made, including audio-visual equipment to implement the e-coaching program.